GAMBARAN FAKTOR–FAKTOR YANG MEMPENGARUHI DEPRESI PADA LANSIA DI POSYANDU LANSIA KAMPUNG TANGGUH KELURAHAN TALISE VALANGGUNI - Nilsa Baubabong; Rabiah Rabiah; Nur Febrianti (Fakultas Ilmu Kesehatan, Universitas Borneo Tarakan, 2022)
Depression is an emotional disorder that is characterized by feeling depressed, not feeling happy, sad, feeling worthless, lacking enthusiasm, meaningless and pessimistic about life. The purpose of this study was to determine the social support that affects the depression of the elderly at the Posyandu for the Elderly in Tangguh Village, Talise Valangguni Village. The research used in this research is quantitative research. The sample population studied was the elderly aged 60 years and the sampling technique used was purposive sampling as many as 17 respondents, namely by following the Posyandu for the Elderly in Tangguh Village, Talise Valangguni. The results showed that the distribution of the 17 studied showed that the distribution of respondents based on social support knowledge was good, namely 17 respondents (100%) the distribution of the 17 respondents studied showed that the distribution of respondents based on family support was mostly good 16 respondents (94.1% ) while the poor category is 1 respondent (5.9%). Elderly with good social support because the elderly still communicate with family and life with neighbors in the vicinity is well established. Conclusion Social support at the Elderly Posyandu in Tangguh Village, Talise Valangguni Village, was obtained well and also the Family Support at the Elderly Posyandu in Tangguh Village, Talise Valangguni Village, was obtained well.